2012
DOI: 10.1017/s1368980012002753
|View full text |Cite
|
Sign up to set email alerts
|

Social health and nutrition impacts of community kitchens: a systematic review

Abstract: Objective: Community kitchens have been implemented by communities as a public health strategy to prevent food insecurity through reducing social isolation, improving food and cooking skills and empowering participants. The aim of the present paper was to investigate whether community kitchens can improve the social and nutritional health of participants and their families. Design: A systematic review of the literature was conducted including searches of seven databases with no date limitations. Setting: Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 15 publications
4
59
0
2
Order By: Relevance
“…According to our data, more than one-third of new participants in alternative interventions are food secure compared to less than one tenth of participants in traditional interventions. Therefore, new participants in alternative interventions may look for specific skill development or social relationship more than to solve urgent needs of food, since the effects of alternative interventions tend to focus upon social or skill based needs [18]. Finally, our study showed that people utilizing the alternative interventions report better health, both physical and mental when compared to participants utilizing traditional interventions.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…According to our data, more than one-third of new participants in alternative interventions are food secure compared to less than one tenth of participants in traditional interventions. Therefore, new participants in alternative interventions may look for specific skill development or social relationship more than to solve urgent needs of food, since the effects of alternative interventions tend to focus upon social or skill based needs [18]. Finally, our study showed that people utilizing the alternative interventions report better health, both physical and mental when compared to participants utilizing traditional interventions.…”
Section: Discussionmentioning
confidence: 63%
“…Although alternative interventions aim to improve food security, studies on collective kitchens have revealed negligible effects on increasing participants' food resources and no effects on improving poverty levels or food security [10,17]. Nevertheless, research has also found that collective kitchens can positively impact other health determinants: support network, nutritional intake, self-esteem, budgeting and cooking skills [18]. Similar findings emerge for community gardens: benefits are primarily related to socializing, learning, building awareness and social responsibility, without a real impact on food security [19].…”
Section: Community Food Security Intervention In Canadamentioning
confidence: 99%
“…Rees et al (2012) suggested current evidence on the effects of cooking courses is inconclusive due to the lack of high quality evaluations and that more evidence is required about impact. Iacovou et al (2012) similarly conclude more rigorous research methods, including both quantitative and qualitative studies, are required to effectively measure the true impact of such interventions on nutritional health. Reicks et al (2014) meanwhile concluded that there was a need for further evidence on the long-term impact of cooking behaviour, dietary intake and health outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…They noted that interventions that include cooking may result in improved food choices, dietary behaviours and other health related outcomes. A further systematic review by Iacovou, Pattieson, Truby and Palermo (2012) concluded that community-based cooking programmes may be effective interventions in improving participants' cooking skills and nutritional intake. Finally, a more recent systematic review of cooking programmes (Reicks et al, 2014) found that qualitative and quantitative measures suggest a positive influence on dietary intake, knowledge, skills, cooking attitudes and health related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies found that although community interventions were able to increase food availability, the rates of participation by food insecure populations were low (Engler-Stringer & Berenbaum, 2007;Hamelin et al, 2011;Iacovou et al , 2013;Loopstra & Tarasuk, 2013). Community ownership and engagement can also be supported in gardening initiatives developed according to the process by Fuertes et al (2012).…”
Section: Community Interventions To Address Food Insecuritymentioning
confidence: 99%